Science in world history - Trefil, James (Themes in world history, 2012)
"Science today is a truly global enterprise. This book is a comprehensive, thematic survey of the history of science from its roots in different cultures around the world through to the present day. James Trefil traces how modern science spread from its roots in Western Europe to the worldwide activity it is today, exploring crucial milestones such as the Copernican revolution, the germ theory of disease, and the theory of relativity. In doing so, he also examines the enormous social and intellectual changes they initiated. Opening with a discussion of the key elements of modern scientific enterprise, the book goes on to explore the earliest scientific activities, moving through to Greece and Alexandria, science in the Muslim world, and then on to Isaac Newton, atomic theory and the major developments of the nineteenth century. After examining the most recent scientific activities across the world, the book concludes by identifying future directions for the field. Suitable for introductory courses and students new to the subject, this concise and lively study reconsiders the history of science from the perspective of world and comparative history"--